Advancing HIV Broadly Neutralizing Antibodies: From Discovery to the Clinic - Spencer, David A.; Shapiro, Mariya B.; Haigwood, Nancy L.; Hessell, Ann J. (Frontiers in Public Health, 2021)
Despite substantial progress in confronting the global HIV-1 epidemic since its inception in the 1980s, better approaches for both treatment and prevention will be necessary to end the epidemic and remain a top public health priority. Antiretroviral therapy (ART) has been effective in extending lives, but at a cost of lifelong adherence to treatment. Broadly neutralizing antibodies (bNAbs) are directed to conserved regions of the HIV-1 envelope glycoprotein trimer (Env) and can block infection if present at the time of viral exposure. The therapeutic application of bNAbs holds great promise, and progress is being made toward their development for widespread clinical use. Compared to the current standard of care of small molecule-based ART, bNAbs offer: (1) reduced toxicity; (2) the advantages of extended half-lives that would bypass daily dosing requirements; and (3) the potential to incorporate a wider immune response through Fc signaling. Recent advances in discovery technology can enable system-wide mining of the immunoglobulin repertoire and will continue to accelerate isolation of next generation potent bNAbs. Passive transfer studies in pre-clinical models and clinical trials have demonstrated the utility of bNAbs in blocking or limiting transmission and achieving viral suppression. These studies have helped to define the window of opportunity for optimal intervention to achieve viral clearance, either using bNAbs alone or in combination with ART. None of these advances with bNAbs would be possible without technological advancements and expanding the cohorts of donor participation. Together these elements fueled the remarkable growth in bNAb development. Here, we review the development of bNAbs as therapies for HIV-1, exploring advances in discovery, insights from animal models and early clinical trials, and innovations to optimize their clinical potential through efforts to extend half-life, maximize the contribution of Fc effector functions, preclude escape through multiepitope targeting, and the potential for sustained delivery.